PELATIHAN QUIZIZZ UNTUK MEDIA PEMBELAJARAN BERBASIS PERMAINAN BAGI GURU DI SMA PGRI BLAHBATUH PLUS PARIWISATA (PARISMA BLAHBATUH) - Ida Ayu Putu Febri Imawati; Ni Luh Putu Risma Noviana; I Wayan Dika; I Nyoman Bagus Suweta Nugraha; Ni Luh Gede Ambaradewi (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
Quizizz training for teachers at SMA PGRI Blahbatuh aims to improve teacher competence in information technology. The training was conducted for one day. Starting from introducing Quzizz in general, making presentations to making quizzes. Based on the training results, trials of using Quizziz independently, and mentoring, teachers have been able to use Quizizz as a learning media.